The Future of Saving : The Role of Pension System Design in an Aging World - Amaglobeli, David; Chai, Hua.; Dabla-Norris, Era.; Dybczak, Kamil (Washington, D.C. : International Monetary Fund, 2019)
This SDN explores how demographic changes have affected and will affect public and private sector savings, highlighting the interaction between pension systems, labor markets, and demographic variables.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet